Meong-meongan as cultural heritage: an ethnographic study of traditional sports games - Handyka Prasetyo; Made Agus Wijaya; I Made Satyawan (Universitas Sriwijaya, 2025)
Research Problems: The lack of literature studies on traditional meong-meongan sports games, such as books in educational units, is the root of this research problem and the lack of preservation of traditional sports. Research Objectives: Describes an ethnographic study of the traditional sports game meong-meongan that takes place in the Tenganan Pegringsingan Traditional Village, Karangasem Regency. Methods: This qualitative research uses an ethnographic approach. Data were collected through observation, interview, and documentation techniques. With the sample, namely Kelian Adat and Village Head of Tenganan Pegringsingan Traditional Village, Karangasem Regency Cultural Office Employees, Chairperson of Portina Bali, and PJOK Teacher of SD Negeri 1 Tenganan. Observation was carried out to find out whether it was true that the traditional sports game meong-meongan originated from the Tenganan Pegringsingan Traditional Village, Karangasem Regency. Documentation was carried out to document photos and videos during interviews and as evidence of having conducted interviews. Data analysis was carried out through several stages, namely data collection, data reduction, data presentation, and conclusion drawing. Results: The research showed that although all five interviewees were familiar with the traditional game meong-meongan, most students did not know about it when it was introduced at school. This indicates that the game is almost unknown among the younger generation, due to a lack of supporting literature and minimal efforts to socialise the game. Conclusion: The findings of this research are that the traditional sports game meong-meongan contains noble cultural values, including elements of education, cooperation, and local wisdom that have been passed down from generation to generation. However, modernisation and a lack of regeneration in the community led to a significant decline in the practice of this game. This research aims to reintroduce the traditional sports game meong-meongan to the younger generation, to preserve the cultural heritage.